Usefulness of a newly developed high-speed polymerase chain reaction analysis system for the diagnosis of Clostridioides difficile infection - Furukawa, Keitaro; Mitsutake, Hiroshi; Aso, Ryoko; Sekizawa, Ryuichi; Okanda, Takashi; Hayashi, Kuniyoshi; Matsumoto, Tetsuya; Nakamura, Shigeki (Journal of Infection and Chemotherapy, 2021)
The incidence of Clostridioides difficile infection (CDI) has been continuously increasing and thereby became an important issue worldwide. Appropriate diagnosis, management, and infection control are required for patients with CDI. Enzyme immunoassay (EIA) is a widely used standard diagnostic tool for C. difficile-specific glutamate dehydrogenase (GDH) and C. difficile toxins (toxins A and B). However, the sensitivity of EIA in detecting C. difficile toxins has been reported to be relatively low, resulting in CDI underdiagnosis. Therefore, nucleic acid amplification tests (NAAT) are recently developed for higher sensitivity/specificity test. In this study, a total of 279 stool samples submitted for CDI diagnosis were examined using an independently developed new high-speed polymerase chain reaction (PCR) device (PathOC RightGene, Metaboscreen). In parallel, results were compared with those of definitive diagnosis and conventional diagnostic methods (EIA, real-time PCR) to assess the inspection accuracy. PathOC RightGene showed high sensitivity (96.7%) and specificity (96.7%). Regarding the measurement time, C. difficile-specific and C. difficile toxin genes were simultaneously detected in approximately 25 min for one sample (including the preprocessing and measurement time). PathOC RightGene has been found to show both excellent sensitivity and rapidity and thus can be used for the reliable and early diagnosis, which are needed for the appropriate management of CDI.